INFORMATION AND REALITY (PROBLEMS OF SEMANTICS AND PRAGMATICS) - Олександр МИХАЙЛЮК; Вікторія ВЕРШИНА (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The relevance of the topic of the article is due to the need for philosophical research into the nature of information as a factor that significantly affects the development of modern society. Understanding the nature of information is important for the study of processes, mechanisms, and technologies in any sphere of social life. The study is based on a semiotic approach, the relationship between information and reality is considered based on the semantic and pragmatic aspects of this problem. The concept of semantic information by Luciano Floridi and the views on the nature of information by Yuval Noah Harari are analyzed. The semantic aspect is understood not only in terms of the “truthfulness” of data, but also in terms of the perception and interpretation of this data by the consumer of information. Information appears as a model of reality, and at the same time information models reality, creating a second, illusory reality. A person exists in a situation of “two realities” (ontological and semiotic). This situation of “two realities” creates numerous philosophical and semiotic problems. Information not only reflects and constructs reality but is also used as a means of influencing consciousness, as a means of control. The modern information society is built on technologies of manipulation of consciousness. This is associated with the peculiarities of the functioning of information in society. In modern culture, information increasingly replaces reality, simulates reality. These are fakes and disinformation, rumors and conspiracy theories, as well as literature and art that exist as an imitation of reality. The media record events less and less often, and more and more often direct them. This is what describes the state of post-truth, when information flows themselves determine what is true and what is not. Information loses touch with reality, information and reality do not intersect or intersect rarely. People are increasingly immersed in this artificial reality, being in the information, virtual world.